Optimizing Regional Budget Planning: The Role of Information Systems and Human Resource Competence in Padang Panjang City - Dwina Indriani, Jennisa; Ihsan, Muhammad; Hurnis, Delfi; Irwan, Sony (Journal of Computer Science, Artificial Intelligence and Communications, 2025)
This study aims to examine the effect of the implementation of the Regional Government Information System (SIPD) application and human resource (HR) capacity on the process of preparing the Regional Revenue and Expenditure Budget (APBD) of Padang Panjang City. The APBD preparation process must comply with applicable laws and regulations as well as the predetermined schedule to avoid delays in its ratification. The implementation of the SIPD application and the competence of the human resources involved in the APBD preparation process can be considered as crucial factors in the budgeting process of local governments. This research was conducted to ensure that stakeholders involved in the APBD preparation process in Padang Panjang City are aware of and can improve the factors that support the preparation process, so that the resulting APBD complies with statutory regulations and can be ratified according to the established timeline. This research employs a quantitative approach to analyze data by describing and illustrating the collected information. The data analysis technique used is Partial Least Square (PLS), with the population consisting of all Regional Work Units (SKPD) in Padang Panjang City and a sample of 50 respondents. The findings of this study indicate that both the implementation of the SIPD application and HR capacity have a positive and significant effect on the APBD preparation process.